2021
DOI: 10.3889/oamjms.2021.6027
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Department of Education Center and Service Provide During Coronavirus Disease-2019 Pandemic: An Experience from Single-Center Hospital

Abstract: BACKGROUND: In the global pandemic of the 2019 coronavirus disease (COVID-19), many countries have reported a decrease in visits to hospitals, and health-care systems around the world are reshaping health protocols. Health service and education in orthopedics are also affected although not at the frontline in dealing COVID-19. METHODS: The data from this study collected from several official databases, including the Indonesian Ministry of Health, Central Java provincial government, general hospital, and orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…11,12,17 Research comparing the availability of a COVID-19-free operation route with the unavailability of a COVID-19free operating route found that the post-operative patient SARS-CoV-2 infection rate was lower level in the COVID-19-free operation route. 12,18,19 It should be noted that COVID-19 infection without a COVID-19free surgical route in post-operative patients is around 5% with a mortality rate of 25%. However, this infection and mortality rate can drop to 0% with the COVID-19free operating route.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,17 Research comparing the availability of a COVID-19-free operation route with the unavailability of a COVID-19free operating route found that the post-operative patient SARS-CoV-2 infection rate was lower level in the COVID-19-free operation route. 12,18,19 It should be noted that COVID-19 infection without a COVID-19free surgical route in post-operative patients is around 5% with a mortality rate of 25%. However, this infection and mortality rate can drop to 0% with the COVID-19free operating route.…”
Section: Discussionmentioning
confidence: 99%
“…The sociological survey was conducted online, in which students were asked to send their responses regarding their preferences about the teaching principles to instructors' emails within 24 hours. To compare the significance of teaching principles between students, Cohen's coefficient was calculated using formula 1 (Nugroho et al, 2021):…”
Section: Methodsmentioning
confidence: 99%
“…A common misunderstanding among many end users is that they are protected from potentially infectious materials when they wear any type of fluidresistant protective equipment [8]. It is mandatory for every healthcare facility, especially with concordant limitation resources mainly PPEs during pandemic, the noticed malpractice and inappropriate attitude due to physical and psychological stress [9]. We aimed to assess infection rate of COVID-19 among HCWs since March 2020, with the beginning of COVID-19 first wave in Egypt and for the following 5 months, at Obstetrics and Gynaecology Hospital one of the Teaching University Hospitals in addition to appraisal of potential risk factors of its transmission.…”
Section: Risk Factors For Transmission Of Infection Amongmentioning
confidence: 99%